When morphometry meets taxonomy: morphological variation and species boundaries in Proboscoida (Cnidaria: Hydrozoa). Issue 2 (9th January 2020) - Cunha, Amanda F; Collins, Allen G; Marques, Antonio C
Abstract: Species delimitation in marine taxa is often problematic given large intraspecific variation. Based on extensive, recently published genetic sampling from specimens of the hydrozoan families Campanulariidae, Clytiidae and Obeliidae, we evaluate morphological variation in this group, correlating morphometric and phylogenetic patterns for species delimitation. Several species of Campanulariidae are confidently delimited based on differences in size (e.g. Bonneviella species, Tulpa tulipifera and Rhizocaulus verticillatus ), while others are re-identified and corroborated based on differences in perisarc thickness (e.g. Silicularia rosea, Orthopyxis and Campanularia species). In Clytiidae, the length and diameter of hydrothecae, height of hydrothecal cusps and perisarc thickness delimit the species Clytia linearis, C. elsaeoswaldae and C. noliformis from others. However, few characters reliably differentiate the clades associated with the nominal species C. gracilis and C. hemisphaerica . In Obeliidae, Obelia geniculata is distinctive in its higher perisarc thickness, and corroborated as a widely distributed species . Obelia longissima and clades refered to O. dichotoma are subtly distinguished, showing a few differences in size and branching of colonies. The taxonomic implications of these results are discussed. With a few exceptions, species can be delimited based on morphometric patterns, once morphological variation is compared.